Defining the Planning Tumor Volume by analyzing Setup of Head & Neck (H&N) Carcinoma in Radiotherapy - Sunnia Shafiq, Hina Manzoor, Hafiz Khush Naseeb Ahmad, Awais ur Rehman, Sadiqullah, Imran Arif, Hashir Saeed, Hamida Naheed, Abdul Basit, Jamila Shuja, Qadeer Ahmad, Shehla Iftikhar (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To find out the setup error of Head and Neck patients treated with Intensity modulated radiation therapy (IMRT) on CLINAC-IX at Center for Nuclear medicine and Radiotherapy (CENAR) Quetta by using inbuilt electronic portal imaging device (EPID) to obtain the setup margin for clinical investigation. Methods: A total of 35 patients of head & neck carcinoma were treated with Intensity modulated radiation therapy (IMRT) total dose of 69.96Gy in 33 fractions at CENAR from 1st January 2021 to 31st December 2022 were consider this retrospective study. PTV margin for different directions (Vertical, lateral &Longitudinal) were analyzed by Van Herk’s formula Results: Data analyzed for calculating the mean displacement in X (Lateral), Y (Longitudinal) and Z (Vertical) directions, from where the mean systematic and random errors derived. These shifts (displacements) used for calculation of the final PTV margins by using Van Herk’s formula. The calculated mean (±SD) systematic errors in the Z (Vertical), X (Lateral) and Y (Longitudinal) and directions were 0.10cm, 0.06cm, and 0.07cm and the mean(±SD) random errors were 0.01cm, 0.004cm and 0.01cm respectively. Conclusion: In our study, less than3 mm is an optimal margin for GTV- PTV for head and neck cancer patients. The reduction in setup margin helps in prognosis of treatment results, reduce radiation related complication in normal tissue and reduce the local recurrence. Imaging guidance techniques is effective tool for setup margin. Keywords: Electronic Portal Imaging Device, Van Herk Equation, Systematic Error, Random Error, Head & Neck Carcinoma,